Thermal Hydraulic Analysis for Different Subchannels of Generic VVER-1200 - Mosaddak Ahamed Zahid; Md. Imam Mehedi; Shamsul Arefin Shibly; A. S. Mollah (International Journal of Nuclear Security, 2024)
The demand for nuclear energy is steadily increasing all over the world. Most nuclear power is used for peaceful applications such as power generation, healthcare, agriculture, food security, industry, and research. One of the primary applications of nuclear energy is the generation of electricity through nuclear power plants based on nuclear reactors. Many developing countries around the world (such as Bangladesh) are moving toward nuclear power plants because they have huge advantages, including low-cost energy, reliable energy sources, zero carbon emissions, and high energy concentration. As a result, the demand for nuclear reactor protection and operational protection of nuclear power plants is growing rapidly around the world. To meet this demand, nuclear reactor safety as well as nuclear reactor safety parameters must be analyzed. Our research included an examination of the turbulent flow of coolant water into different subchannels of the VVER-1200 nuclear reactor at a pressure of approximately 16 MPa. The Rooppur Nuclear Power Plant, which is currently being built at Ishwardi, an upazila (i.e., subdistrict) of the Pabna District on the bank of the river Padma in Bangladesh, has a VVER-1200 reactor with geometry details of fuel rods, a coolant subchannel, and other operating parameters that are similar to those of that reactor. We used the ANSYS turbulence model to analyze the three subchannels—central, corner, and edge—using three fuel rods. The effects of turbulent flow on temperature distribution, velocity variance, pressure drop, friction factor, Reynolds number, and more were examined in different subchannels of the VVER-1200. The thermal-hydraulic characteristics of coolant water were also investigated to evaluated safety concerns, such as hot spots in the coolant channel and departure from nucleate boiling.
Keywords: Reynolds number; subchannel; turbulent flow; friction factor; k–ω; departure from nucleate boiling; shear stress transport; k–ϵ